Innovando el financiamiento de proyectos : una aproximación al project finance - Dañino Sinclair, Gabriela; Delgado Sigüeñas, Luis Esteban; Gjurinovic Pacheco, Andrés; Stucchi López-Raygada, Romina; Vargas Villanueva, Claudia (IUS ET VERITAS, 2005)
El artículo no presenta resumen.